High electrical and thermal conductivities of a PAN-based carbon fiber via boron-assisted catalytic graphitization. (31st October 2022) - Lee, Sora; Cho, Se Youn; Chung, Yong Sik; Choi, Young Chul; Lee, Sungho
Abstract: The boron-assisted catalytic graphitization of carbonaceous materials is an attractive methodology for enhancing their electrical properties by modulating the chemical structures of pristine carbons. In this study, polyacrylonitrile-based carbon fibers (CFs) with highly developed microstructures were prepared by boron-assisted catalytic graphitization. Hydrothermally immersed CFs in boric acid were heat-treated up to 2700 °C, and their chemical structures were traced to investigate the boron-assisted catalytic graphitization mechanism. Boron from the gasified boron-related functional groups of CFs diffused into the CFs to form boron carbide, B4 C. The boron-substituted CFs exhibited a highly developed crystalline structure that could not be achieved by heat treatment alone, indicating that boron accelerated the graphitic carbon structure. As a result, boron-assisted catalytic graphitization at 2700 °C simultaneously enhanced the electrical and thermal conductivities of CFs, with values of 3677.8 S/cm and 365.9 W/mK, respectively, which were 2.8 and 2.4 times higher than those of heat-treated CFs at 2700 °C. In addition, CFs were used to prepare CF papers using a wet-laid process, and their heat generation and thermal management capabilities were evaluated. Considering affordable CFs compared to nanomaterials, we believe that our study provides a feasible approach for fabricating heating elements and heat sinks. Graphical abstract: Image 1